If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = (x + 1) + -2x Reorder the terms: 6 + 4x = (x + 1) + -2x Reorder the terms: 6 + 4x = (1 + x) + -2x Remove parenthesis around (1 + x) 6 + 4x = 1 + x + -2x Combine like terms: x + -2x = -1x 6 + 4x = 1 + -1x Solving 6 + 4x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + 4x + x = 1 + -1x + x Combine like terms: 4x + x = 5x 6 + 5x = 1 + -1x + x Combine like terms: -1x + x = 0 6 + 5x = 1 + 0 6 + 5x = 1 Add '-6' to each side of the equation. 6 + -6 + 5x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 1 + -6 5x = 1 + -6 Combine like terms: 1 + -6 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| lx-6l=8 | | 25y^2-166y-70= | | 1.4+0.4= | | 64m^2+4/9 | | 2.8+39.4+22.4= | | 0.1x-1.8= | | 25y^3-166y^2-70y= | | 2y-9=-2-4y | | 42a^2b+95ab-25b= | | -18-4(t-5)= | | ln(x-2)=0.5 | | 9m^3-15m^2=0 | | -6+12p=3p-3+8p | | [2,4,5]-[5,6,7]=0 | | -8-16n+14n-4=5n-4 | | x^2-8xy-20y^2=0 | | 25x+20=-6x-12-x | | 4t+5(1-2t)= | | m^2-14mn-32n^2=0 | | (x+1)(4x-6)=24 | | a^2-ab-2b^2=0 | | 24=24v+24-32+8v | | X-36=102-32 | | (x^2/45)+(14x/45)+1=0 | | 2(3.5n+6)=3.5n-2 | | (5x+3y)(2y+3x)=8 | | 13=-7a-56-6a+4 | | x^2-17x+62=0 | | 18e-(6)=0 | | 41=-1+3n+49n+42 | | (1/3)p=(1/4)p | | -2x+4=5-3 |